Surface-enhanced Raman scattering-active desert-rose-like Ag mesoparticles prepared using cyclic voltammetric methods. Issue 113 (2nd November 2015) - You, You-Hong; Lin, Yang-Wei; Chen, Chung-Yu
Abstract : Desert-rose-like Ag mesoparticles prepared by cyclic voltammetric method possess excellence SERS-activity, reproducibility, thermal stability and aging behavior. Abstract : Desert-rose-like Ag mesoparticles were deposited on a screen-printed carbon electrode substrate through a cyclic voltammetric process in aqueous AgNO3 containing Au nanoparticles. The prepared mesoparticles were characterized using scanning electron microscopy, energy dispersive X-ray spectroscopy, surface-assisted laser desorption/ionization mass spectrometry, X-ray photoelectron spectroscopy, and high-resolution X-ray diffractometry. In addition, the potential for applying these mesoparticles in surface-enhanced Raman scattering (SERS) was investigated. The prepared mesoparticles exhibited a more intense SERS signal (34.3 times) than did irregularly shaped Ag particles because of their extremely intense local electromagnetic fields. The enhancement factor of 4-mercaptobenzoic acid molecules on these mesoparticles was approximately 10 5 . Furthermore, SERS spectra of 4, 4′-dimercapto-azobenzene, 5, 5′-dithiobis-2-nitrobenzoic acid, and Cy3 dye modified DNA were obtained using these mesoparticles; moreover, hot spots for most of the enhanced SERS signals were easily obtained. The thermal stability and aging behaviour of the prepared Ag mesoparticles were higher than those of irregularly shaped Ag particles.